1980
DOI: 10.1055/s-2007-1021710
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Carcinoma of the Esophagus Macroscopic Study with Particular Reference to the Lugol Test

Abstract: The results presented here concern the study of in situ cancer and marked dysplasia revealed during the pathological study of 39 specimens removed during esophagogastrectomy for invasive carcinoma of the esophagus. In 12 cases, macroscopic study made it possible to define precisely the macroscopic features of in situ canccer; in one case, however, the mucous membrane at the site of the in situ cancer was macroscopically normal. The iodine test performed in 37 cases showed that the normal esophageal mucosa is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
3

Year Published

1981
1981
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…Recently, superficial esophageal neoplasias in the squamous epithelium or in the metaplastic columnar mucosa (Barrett's esophagus) could be detected by using chromoendoscopy with iodine staining and narrow-band imaging (NBI) [6][7][8][9]. Although EMR techniques such as the lift-and-cut method, the cap method, and the ligation technique have been widely used to resect superficial esophageal neoplasias, especially squamous cell neoplasias, en bloc resection for larger lesions was considered infeasible.…”
mentioning
confidence: 99%
“…Recently, superficial esophageal neoplasias in the squamous epithelium or in the metaplastic columnar mucosa (Barrett's esophagus) could be detected by using chromoendoscopy with iodine staining and narrow-band imaging (NBI) [6][7][8][9]. Although EMR techniques such as the lift-and-cut method, the cap method, and the ligation technique have been widely used to resect superficial esophageal neoplasias, especially squamous cell neoplasias, en bloc resection for larger lesions was considered infeasible.…”
mentioning
confidence: 99%
“…In one of these studies, we found that the majority (73%) of the biopsies of high grade (moderate and severe) squamous dysplasia and all biopsies of invasive squamous cell carcinoma came from endoscopically visible mucosal lesions, but a significant minority (27%) of the sites containing high grade dysplasia could not be identified visually by routine endoscopic examination. 6 For several years, Japanese and European authors have reported that staining the esophageal mucosa with Lugol's iodine solution can make the presence and extent of squamous dysplastic and cancerous foci more clear, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] but this technique has not often been used by Chinese or American endoscopists. The purpose of this study was to evaluate whether mucosal iodine staining could improve the detection and delineation of high grade squamous dysplasia and squamous cell carcinoma of the esophagus in Linxian.…”
mentioning
confidence: 99%
“…Another method of anatomopathologic examination was proposed by Mandard et al, in 1980 (Mandard et al, 1980). It consists of painting all macroscopically visible lesions as well as those discovered by vital staining with green China ink; this makes all the pathologic zones immediately obvious on the histologic slides.…”
Section: Histology Methodsmentioning
confidence: 99%